Editorial - Vogt, Burkhard; Jörg, Linstädter (Journal of Global Archaeology, 2020)
The Journal of Global Archaeology (JoGA) reflects with its name the KAAK’s worldwide research approach. It replaces the Zeitschrift für Archäologie Außereuropäischer Kulturen (ZAAK), whose last issue was published in 2017. The foundation of JoGA takes into account the requirements of modern scientific communication in every respect. This entails a system for quality assurance (peer review) and the immediate availability of every article to anyone interested (open access).